A mobile dual-arm manipulation robot system for stocking and disposing of items in a convenience store by using universal vacuum grippers for grasping items. (16th February 2020) - Sakai, Ryo; Katsumata, Shinichi; Miki, Takahiro; Yano, Taiki; Wei, Wenpeng; Okadome, Yuya; Chihara, Nobuhiro; Kimura, Nobutaka; Nakai, Yusuke; Matsuo, Isamu; Shimizu, Toshihiko
ABSTRACT: A mobile dual-arm robot with universal vacuum grippers (UVG) for performing stocking and disposing tasks was developed. The robot grasps items in the tasks by using UVGs whose surface adapts to the various shapes of the items. A selection algorithm that determines whether the robot should use one or both manipulators to arrange an item was also developed. A 'reachable-grasp pose' is defined as a pose in which the robot's UVG can easily place an item with a target attitude if it grasps the item. By using the selection algorithm, the robot re-grasps the item by adopting the reachable-grasp pose if the two manipulators do not collide when one is in the current grasp pose and the other is in the reachable-grasp pose. The robot system won the third prize of the Future Convenience Store Challenge 2018. In experiments on stocking and disposing tasks, the robot system achieved success rates of 100% for the stocking task and 80% for the disposing task. We believe that the results of this study will help researchers to develop a robot system for not only the stocking and disposing tasks but also other tasks in convenience stores (like customer interaction). GRAPHICAL ABSTRACT: